Condemnation and Financial Loss due to Ovine and Bovine Liver Abscesses and Necrosis in the Sudan - Osman, E. Hind; Elsir, B.; Ebrahim, Mohamed T. (Newest Updates in Agriculture and Veterinary Science Vol. 3, 2023)
Livers are well-known for its high nutritional value. In Sudan, they are eaten raw as a food habit. Surveys regarding liver abscesses and necrosis in ovine and bovine livers were carried out to reflect their magnitude and economic impact. The effect of the season on those affections was studied. Prospective study at different periods during 1994 and 1995 and retrospective studies for the whole seven years from 1996 to 2002 were carried out to study liver condemnation of slaughtered cattle and sheep in Omdurman Central Abattoir and Elsabalouga Abattoir respectively. Liver condemnations due to different affections during the period 1994-1995 were found to be 26.2% in sheep and 5.4% in cattle; Out of those condemnations, 57.6 % and 22% respectively were found to be due to abscesses and necrosis. While during the period 1996-2002, out of the 15.45 condemned ovine livers, 77.43% were condemned due to abscesses and necrosis and Out of the 10.69% of the bovine condemned livers, 11.96% were condemned due to abscesses and necrosis. The number of total condemned ovine and bovine livers and the condemnation for necrosis and abscesses were strongly to moderately correlated. It was discovered that the ovine and bovine liver condemnations were not significantly impacted by the seasons.